Junie B. Jones and the Yucky Blucky Fruitcake : Junie B. Jones #5 - Park, Barbara, 1947-; Brunkus, Denise (New York : Random House, 1995)
Junie, a spunky, sometimes exasperating, kindergartener, looks forward to winning lots of prizes at the school carnival, but a fruit cake was not exactly what she had in mind.
"A first stepping stone book."
"RL: 2.1"--Cover p. [4].
Accelerated Reader
Keywords: Kindergarten -- Fiction; Schools -- Fiction; Carnivals -- Fiction; Behavior -- Fiction; Kindergarten -- Fiction; School stories; Carnivals -- Fiction; Human behavior -- Fiction